Penerapan Metode Kooperatif Jigsaw dalam Meningkatkan Minat Belajar Materi Akhlak Pendidikan Agama Islam Kelas VII SMP Ar-Riyadh Bontang Tahun Pelajaran 2024/2025 - Imam Syauqi, Bariq; Murni, Murni (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
In the learning process in class, it was found that some students paid less attention to the teacher's explanation, did not take notes on the lesson material, daydreamed and fell asleep during the learning process. This study aims to determine the application of the Jigsaw cooperative method in increasing interest in learning the Morals material in the Islamic Religious Education (PAI) subject of class VII students of SMP Ar-Riyadh Bontang in the 2024/2025 Academic Year. This type of research is qualitative research, descriptive approach. The research data are primary and secondary data collected using observation, interview, and documentation data collection techniques. The results of the study showed that the application of the Jigsaw cooperative method was able to significantly increase students' interest in learning. Students become more active, responsible, and motivated in following the lesson. The Jigsaw method makes students feel they have an important role in their study group. In the learning process, students work together, discuss, and convey material to their group members. This makes the learning atmosphere more enjoyable and meaningful. The increase in interest in learning can be seen from several indicators, including: increasing student interest in morals material, increasing student attention in the learning process, and the emergence of motivation from within students to learn and understand the material in more depth. In addition, social interaction between students also improved due to cooperation in groups. From the results of this study, it can be concluded that the Jigsaw cooperative method is effective in increasing students' interest in learning Islamic Religious Education subjects, especially moral material. It is hoped that this method can be an alternative learning strategy that is fun and interactive in schools.